Graftless immediate implant placement in the extremely atrophic posterior maxillary site utilizing lateral window and tenting approach followed by surgicel aided closure: A case report with 1-year follow-up - Rahul Deshwal; Sanjeev Kumar Salaria; Neha Deshwal (Journal of Indian Society of Periodontology)
The maxillary sinus is the largest among paranasal sinuses, lined with Schneiderian membrane having an innate osteogenic potential. The alveolar ridge resorption and pneumatization of the maxillary sinus are inescapable findings postextraction, which may diminish the vertical bone dimensions needed for endosteal implant placement. To overcome these problems, maxillary sinus augmentation using bone grafting materials has been advocated but the cost of graft materials, chances of graft contamination, graft allergy, etc., are the disadvantages/risks associated with it. In order to accomplish passable density of stable peri-implant bone, which aids in increasing implant primary stability; Densah bur-assisted osseodensification approach is highly recommended. To improve Schneiderian membrane, osteogenic potential and bone volume platelet-rich fibrin (PRF) are advocated. The present case described the successful outcome of single-stage graftless immediate implant placement in the edentulous maxillary first and second molar region with ≤3–4 mm of vertical alveolar bone height utilizing lateral window and implant with PRF plug as well as PRF membrane-assisted tenting approach at 1-year follow up.